Development of food grade green lubricant from palm oil methyl ester - Mohamad Aziz, Nur Atiqah (2015)
Food grade lubricant is compulsory in food processing industry when there is a possibility for the lubricant to come into contact with a food product. Mineral-based oil is not safe and may contaminate food after contact. However, the commercially available food grade lubricants are expensive. In this study, the potential of using pentaerythritol ester as the base oil in the food grade lubricant was investigated. The synthesis of pentaerythritol ester was conducted using the transesterification process between palm oil methyl ester (PME) and pentaerythritol (polyol) producing pentaerythritol ester with mostly tetra ester structure. The optimization process of the transesterification reaction was assisted by response surface methodology (RSM) - central composite rotatable design (CCRD). Four factors were studied; temperature (140 - 190˚C), catalyst amount (0.5 – 1.5 wt % w/w), PME-to-pentaerythritol molar ratio (4:1 – 5:1) and duration (1 – 5 hr) to produce the maximum amount of pentaerythritol tetra ester. The optimum operating conditions were at 158˚C, catalyst amount 1.19%, molar ratio 4.5:1 and 1 hour reaction duration resulted in 40.13% of tetra ester. Additives approved by Food and Drug Administration (FDA) and United State Department of Agriculture (USDA) such as antioxidant (Irganox L 57), antiwear (Irgalube 349) and corrosion inhibitor (Irgamet 39) were added at different composition and combination to enhance the base oil properties. Four formulated pentaerythritol esters were tested for oxidative stability test, four-ball test, and flash point test, of which the results showed comparable characteristics with a commercial chain lubricant. Acute toxicity test was also carried out to prove that the pentaerythritol ester is non-toxic. Among the formulated oils, a sample name Anti Wear Corrosion Inhibitor (AWCI) which comprised of 0.15 % Irgalube 349, 0.15 % Irgalube TPPT, and 0.1 %Irgamet 39, was chosen as the best formulation. AWCI exhibits high flash point, has better oxidative stability and excellent wear properties.